Epigallocatechin-3-gallate Ameliorates Seawater Aspiration-Induced Acute Lung Injury via Regulating Inflammatory Cytokines and Inhibiting JAK/STAT1 Pathway in Rats - Wei Liu; Mingqing Dong; Liyan Bo; Congcong Li; Qingqing Liu; Yanyan Li; Lijie Ma; Yonghong Xie; Enqing Fu; Deguang Mu; Lei Pan; Faguang Jin; et al. (Hindawi Limited, 2014)
Signal transducers and activators of transcriptions 1 (STAT1) play an important role in the inflammation process of acute lung injury (ALI). Epigallocatechin-3-gallate (EGCG) exhibits a specific and strong anti-STAT1 activity. Therefore, our study is to explore whether EGCG pretreatment can ameliorate seawater aspiration-induced ALI and its possible mechanisms. We detected the arterial partial pressure of oxygen, lung wet/dry weight ratios, protein content in bronchoalveolar lavage fluid, and the histopathologic and ultrastructure staining of the lung. The levels of IL-1, TNF-α, and IL-10 and the total and the phosphorylated protein level of STAT1, JAK1, and JAK2 were assessed in vitro and in vivo. The results showed that EGCG pretreatment significantly improved hypoxemia and histopathologic changes, alleviated pulmonary edema and lung vascular leak, reduced the production of TNF-α and IL-1, and increased the production of IL-10 in seawater aspiration-induced ALI rats. EGCG also prevented the seawater aspiration-induced increase of TNF-α and IL-1 and decrease of IL-10 in NR8383 cell line. Moreover, EGCG pretreatment reduced the total and the phosphorylated protein level of STAT1 in vivo and in vitro and reduced the phosphorylated protein level of JAK1 and JAK2. The present study demonstrates that EGCG ameliorates seawater aspiration-induced ALI via regulating inflammatory cytokines and inhibiting JAK/STAT1 pathway in rats.